Views on the Methodology of Harmonizing between wholeness of time and wholeness of Sharia and faith (Islamic Sciences Journal, 2023)
This research paper is an attempt to lay down a methodological framework for controlling the balances of dealing with the challenges facing Islamic jurisprudence by drawing a set of methodological schemes that are represented by looking at cases of tensions between faculties and parts. To overcome a methodological defect, the most prominent of which is the case of the segmentation, which is represented by inferring the partial text and leaving other texts that may restrict its release and specialize its generalisation and interpretation of its entireness, as well as the partial inference and symptoms about the whole.We explained in the research the methodological pathways that control the instances of tension and how to harmonize them with the texts of Sharia in a way that does not contradict or isolateThen we came to many proven results at the end of the research.